Clariant develops new oxygen scavenger for packaging applications. Issue 2 (February 2015) - Unknown
Abstract : Switzerland's speciality chemicals company Clariant reports that it has developed a new oxygen-scavenging masterbatch for use in polyethylene terephthalate (PET) packaging applications. The latest addition to its Cesa®-absorb product range, the novel masterbatch has an integrated active oxygen barrier that 'optimally protects' sensitive packaged goods from oxygen-induced degradation, thereby extending shelf-life and reducing food and beverage waste, the company says.